FREDERIK KORTLANDT: SELECTED WRITINGS ON SLAVIC AND GENERAL LINGUISTICS - Sukač, Roman (Slavia Centralis, 2020)
V prispevku je predstavljena knjiga Frederika Kortlandta z naslovom Selected Writings on Slavic and General Linguistics (2011).